EFEKTIVITAS METODE TABARAK DALAM MENGHAFAL SURAT AN-NABA ANAK USIA 3 TAHUN DI RUMAH TAHFIDZ BALITA DAN ANAK KOTA MALANG - Salsabila Firdausi Nuzula; Maskuri Maskuri; Kukuh Santoso (VICRATINA, 2021)
Various kinds..of..methods in memorizing Al-Qur'an that appear nowadays aim to make..it..easier for children to memorize Al-Qur'an, one of those methods is Tabarak method in which it is used for early childhood in memorizing Al-Qur’an. Tabarak method is applied for children with the aged of 3 at Rumah Tahfidz Balita dan Anak Kota Malang, it is used to measure the effectiveness of memorizing Surah An-Naba’ for children. Quantitative descriptive was used as the researh design in this present study; moreover, the method used to take the sample was total sampling of all students with the aged of 3, totalling 18 students at Rumah Tahfidz Balita dan Anak Kota Malang. This present study used simple regression analysis on SPSS to analyze the data. Confirming the results of hypothesis testing with R value of 75%, it proves that there is an effectiveness of Tabarak method in memorizing Surah An-Naba’ in children aged of 3. Meanwhile, the R-Square value 57.3% represents the contribution of the effectiveness of Tabarak method in memorizing Surah An-Naba' in children with the aged of 3. The other result shows that Tabarak Method in memorizing Surah An-Naba’ in children with the aged of 3 is declared effective.